2013
DOI: 10.1007/jhep09(2013)125
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly mediation from unbroken supergravity

Abstract: When supergravity (SUGRA) is spontaneously broken, it is well known that anomaly mediation generates sparticle soft masses proportional to the gravitino mass. Recently, we showed that one-loop anomaly-mediated gaugino masses should be associated with unbroken supersymmetry (SUSY). This counterintuitive result arises because the underlying symmetry structure of (broken) SUGRA in flat space is in fact (unbroken) SUSY in antide Sitter (AdS) space. When quantum corrections are regulated in a way that preserves SUG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 76 publications
(340 reference statements)
0
36
0
Order By: Relevance
“…The second puzzle concerns the goldstino couplings. The XW 2 α interaction contains a goldstino coupling, which is not expected in strict gravitino mediation [6,7]. The resolution is that the microscopic theory breaks SUSY by a small amount F Q ∼ vW 0 .…”
Section: Jhep02(2014)069mentioning
confidence: 96%
See 2 more Smart Citations
“…The second puzzle concerns the goldstino couplings. The XW 2 α interaction contains a goldstino coupling, which is not expected in strict gravitino mediation [6,7]. The resolution is that the microscopic theory breaks SUSY by a small amount F Q ∼ vW 0 .…”
Section: Jhep02(2014)069mentioning
confidence: 96%
“…[6,7] have analyzed anomaly mediation in detail and demonstrated that there are several distinct mechanisms at work, physically separable by the JHEP02(2014)069 goldstino coupling to the supercurrent. The gaugino mass contributions we will identify correspond to pure gravitino mediation in the language of [6,7], although as we will see the issue of the goldstino coupling is somewhat subtle. The masses we study are bulk AdS masses, which are equivalent to the flat-space masses when the SUSY-breaking is sequestered from the visible sector (see also footnote 1.)…”
Section: Jhep02(2014)069mentioning
confidence: 99%
See 1 more Smart Citation
“…As emphasized above, the form of this coupling is fixed by some contact terms in the correlators of the energy-momentum tensor multiplet and it is necessary even if supergravity is non-dynamical. It has to be included when analyzing supersymmetric theories in curved space (for a discussion from a different point of view in the case of AdS 4 , see also [17,18]). In flat space, if SUSY is broken in the hidden sector B, we need to turn on a VEV for M in order to cancel the cosmological constant.…”
Section: Jhep04(2014)073mentioning
confidence: 99%
“…If the vacuum is supersymmetric, it is eventually canceled by infrared dynamics. In [17,18] the central idea is that the anomaly mediated contribution (for example, the gaugino mass or the A-term) is actually supersymmetric under a deformed SUSY algebra characteristic of AdS 4 space. Several aspects of these derivations have to be contrasted with the main features of our approach, which we now summarize:…”
Section: Jhep04(2014)073mentioning
confidence: 99%